PENGARUH LETAK MARGIN PREPARASI DAN TEKNIK PENYINARAN TERHADAP KEBOCORAN MIKRO PADA DINDING GINGIVAL RESTORASI RESIN KOMPOSIT KAVITAS KELAS II - , Anisatus Sholichah, Drg. Endang Retnowati, Sp.KG(K)., M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The aim of this study was to investigate the effect of position preparation margin and curing technique on the microleakage at gingival wall class II resin comnposite restoration. Twenty human maxillary extracted premolar teeth were used in this study. A crossbar cavity preparation (3x2x4mm) with the distance 1 mm at coronal CEJ and 1 mm at apical CEJ. The subject of this study is divided to four groups : Group I is preparation margin at enamel, fast curing technique